Making Ready-To-Wear Clothing Decorated with Songket Batubara Ornaments Using Embroidery Techniques at Yati Modiste - Armaini Rambe; Hilma Harmen; Juliarti; Erni (LPPM Universitas Muhammadiyah Tasikmalaya, 2024)
The aim of the activity is to maintain Yati Modiste's business in facing the pandemic by making ready-to-wear clothing decorated with Batubara songket ornaments using embroidery techniques. Mitra is a tailor at Yati Modiste, Barung - Barung Village, Limapuluh District, Batubara, North Sumatra. The output of the activity is three ready-to-wear clothes decorated with Batubara songket ornaments using embroidery techniques, development of an effective business management system, online marketing and articles resulting from the activity. This activity is carried out using a persuasive-educative approach through counseling and training stages. The methods used are lecture, demonstration, question and answer methods which include preparation, implementation, evaluation. and monitoring. The results of the activity obtained were that participants were able to make six ready-to-wear clothes decorated with Batubara songket ornaments using embroidery techniques. The impact of this activity is to increase the income of tailors at Yati Modiste